Psychometric evaluation of Stanford health assessment questionnaire 8-item disability index (HAQ 8-item DI) in elderly people - Zahra Tagharrobi; Khadije Sharifi; Zahra Sooky (Guilan University of Medical Sciences, 2014)
Introduction: Measuring level of disability in elderly in attention to their physical status requires an instrument practicable in elderly and easy to score. Objective: Survey the reliability and validity of the HAQ 8-item DI in older people residing in Kashan Golabchi nursing home. Methods: In this methodological study, samples were chosen by census method (n=100). After translation of original copy, the inter-rater agreement between evaluators and internal consistency were assessed. For validity determination, concurrent validity, exploratory factor analysis and Known-groups were used. The data were analyzed using Pearson correlation coefficient, Intra-class correlation coefficient (ICC), Kappa, Equal - Length spearman-brown, Guttman, Alpha Cronbach coefficient, Kruskal-Wallis test and factor analysis via principal component analysis with varimax rotation. Results: Inter-rater reliability coefficient for every item was good or excellent (Kappa>0.7). ICC in relation to overall instrument was 0.992. The questionnaire reliability coefficient (internal consistency) was 0.95-0.98. Item-total correlation confirmed its reliability too. Its concurrent validity with original Barthel index was confirmed (r=-0.92, p<0.0001). The known-groups approach revealed this tool as valid (p<0.0001). The factor analysis extracted one main factor with value more than one which could explain %87.15 of the total variance of elderly disability. Conclusion: The Persian translation of HAQ 8-item DI for evaluation of disability in elderly people residing in Golabchi nursing home is valid and reliable.